The Relationships Between Costs and User Charges: The Case of a Norwegian Utility Service - Lars-Erik Borge; Jørn Rattsø (Center for Economic Studies and ifo Institute (CESifo), 2003)
The paper investigates the relationships between costs and user charges in the sewage industry in Norwegian local governments. The purpose of the analysis is to answer the following questions: (i) To what extent is a higher unit cost passed on to consumers in terms of a higher user charge? (ii) Does user charge financing lead to higher or lower unit cost? The econometric analysis indicates that around 40 per cent of a cost increase is passed on to consumers in terms of higher user charge. Moreover, user charge financing has a significant negative effect on the unit cost. An increase in the degree of user charge financing by 10 per cent-points is predicted to reduce the unit cost by 5-8 per cent.
Keywords: 330; cost control; user charges; sponsor-bureau model; utility service